A comparative study on the effect of periodontal surgery and conventional periodontal therapy on reduction of serum concentration of C-reactive protein - Jalalaldin Hamissi; Pedram Khajooei (Isfahan University of Medical Sciences, 2011)
Introduction: Aggressive periodontitis is associated with widespread systemic inflammation. C-reactive protein is known as a mediator capable of establishing a connection between periodontal disease and several systemic diseases. Some studies have shown that C-reactive protein is superior to cholesterol in predicting cardiovascular problems and death as a result of cerebrovascular accidents. Previous studies have demonstrated the relationship between periodontitis and high serum levels of C-reactive protein in various societies. The present study compared the effect of periodontal surgeries and conventional non-surgical treatment modalities on C-reactive protein level variations in patients with moderate-to-advanced generalized periodontitis.Materials and Methods: In this clinical trial, 80 systemically healthy individuals with an age range of 28-37 years, who had moderate-to-advanced generalized periodontitis, were selected and divided into two equal groups of 40. One group was treated by conventional periodontal modality (scaling) and the other was treated by surgery. The subjects' medical and periodontal parameters, including C- reactive protein serum levels, pocket depth, bone loss and clinical attachment loss, were measured before and six months after treatment. Data was analyzed by SPSS 15 software using independent and paired t-tests (α = 0.05).Results: The results showed that both treatment modalities decreased C-reactive protein serum levels, with the surgical treatment having a greater role in the decrease without any significant differences. Both treatment modalities significantly decreased pocket depths, but there was no significant reduction in the attachment loss and bone loss.Conclusion: It appears surgical periodontal treatment results in a greater decrease in C-reactive protein levels compared to non-surgical techniques but further studies are necessary. Key words: Alveolar bone loss, C-reactive protein (CRP), Periodontitis